Neo-Marxism, development and underdevelopment - Stone, Carolyn Michele (Department of Political Studies, 2016)
This thesis sets out to achieve two major objectives: firstly, it aims to describe and discuss the background to and the distinctive features of neo-Marxist theories of development and underdevelopment; and secondly, it attempts in a brief case study to demonstrate that a neo-Marxist approach can be fruitfully applied to a study of development and underdevelopment in South Africa. By "neo-Marxism" the writer means that body of thought which, although rooted in traditional Marxism, attempts to come to terms with the relative success of Marxism in the underdeveloped world and its relative lack of success in the developed world. In the 1840's Marx and Engels expected socialism to be established in the most "advanced " countries. This was to be followed by the emancipation of the more "backward" nations. The emancipation of Ireland, for example, was to be achieved through the victory of socialism in Britain. But when British capitalism continued to develop, integrating the proletariat into this development, Marx and Engels turned towards the periphery, to Poland and Russia in the East and to Ireland and the United States in the West. The story of the development of neo-Marxism is the story of the socialist rise of the underdeveloped world, first in theory and then in practice.